Cannabis Use during Adolescent Development: Susceptibility to Psychiatric Illness - Chadwick, Benjamin; Miller, Michael L.; Hurd, Yasmin L. (Frontiers in Psychiatry, 2013)
Cannabis use is increasingly pervasive among adolescents today, even more common than cigarette smoking. The evolving policy surrounding the legalization of cannabis reaffirms the need to understand the relationship between cannabis exposure early in life and psychiatric illnesses. Cannabis contains psychoactive components, notably Δ9-tetrahydrocannbinol (THC), that interfere with the brain’s endogenous endocannabinoid system, which is critically involved in both pre- and post-natal neurodevelopment. Consequently, THC and related compounds could potentially usurp normal adolescent neurodevelopment, shifting the brain’s developmental trajectory towards a disease-vulnerable state, predisposing early cannabis-users to motivational, affective and psychotic disorders. Numerous human studies, including prospective longitudinal studies, demonstrate that early cannabis use is associated with major depressive disorder and drug addiction. A strong association between schizophrenia and cannabis use is also apparent, especially when considering genetic factors that interact with this environmental exposure. These human studies set a foundation for carefully controlled animal studies which demonstrate similar patterns following early cannabinoid exposure. Given the vulnerable nature of adolescent neurodevelopment and the persistent changes that follow early cannabis exposure, the experimental findings outlined should be carefully considered by policymakers. In order to fully address the growing issues of psychiatric illnesses and to ensure a healthy future, measures should be taken to reduce cannabis use among teens.